Vocal Apparatus Structure of the Sarawak Frogs (Amphibia: Anura: Ranidae) - Elvy, Quatrin Deka; Lela, Su’ut; Hasnizam, Abdul Wahid; Ramlah, Zainudin (Universiti Kebangsaan Malaysia, 2015)
Studies have shown that some characters, such as morphological, biochemical and behavioural characteristics were shared among con-specifics of closely related frog species. It is hypothesized that closely related frogs would have similar vocal apparatus structure to produce similar call characteristics, in order to be recognized by con-specifics. The vocal apparatus structures of the frogs from Ranidae were, thus, investigated and calls were recorded from various locations in Sarawak, Borneo. The vocal apparatus was sliced and stained using haematoxylin and eosin staining method. The prepared slides were scanned using Dotslide System Olympus BX51. Captured images were further measured using Microscope Olympus BX51. The results showed that the vocal apparatus structure of ranids in Sarawak differed in length between pulvinar vocale and posterior margin (pvpm) or known as vocal cord stricter. This character was deemed to be the most significant character to discriminate the Sarawak ranids. It is suggested that histological analysis is also a good method for study of phenotypic variation of frog species, as shown by the vocal apparatus structure of the anurans. This study provides an alternative method to differentiate taxonomic identity among frog species.